Does intercropping maize with forage sorghum effect biomass yield, silage bromatological quality and economic viability? (Research, Society and Development, 2020)
Maize and forage sorghum crops have a relevant economic importance in Midwest Brazil and there is a need for more information for their intercropping as a strategy for the farmers to reduce inputs. The objective of this work is evaluate if forage sorghum and maize intercropping effects agronomic traits, the bromatological characteristics of silage from the consortium at different times of silo openings, and the economic viability of all crop systems. This experiment was carried on in the field with seven treatments, consisting of monoculture and intercropping of corn and sorghum hybrids. Monoculture of sorghum Agri 001 and maize Agri 320, as well as in maize Agri 320, Agri 340 and Agri 104 intercropped with sorghum Agri 001 had the highest biomass yield. Intercropped maize did not have lodging, reduction in height, nor decrease in the first ear height in relation to the intercropped plants. Maize hybrids intercropped with sorghum led to a better fermentation pattern of silages, reducing ammonia concentrations. However, due the higher contents of NDF and the lower TDN contents of sorghum, nutritional values of intercropped silages were generally smaller than when they were composed only with maize. It was observed that the monoculture of sorghum Agri 001 for silage showed a higher profit compared to the other treatments.